Mitochondrial iron transporter ClMrs3/4 regulates iron homeostasis to modulate nitric oxide balance facilitating appressorial development in Curvularia lunata - Sun, Jiaying; Huang, Hongming; Li, Jiayang; Xu, Jingru; Jia, Jiaqi; Li, Wenling; Cheng, Jie; Zhu, Dongyu; Liu, Miaomiao; Yuan, Mingyue; Xiao, Shuqin; Xue, Chunsheng (New Phytologist, 2025)
Iron is indispensable for the vast majority of organisms, and iron homeostasis plays a pivotal role in both the physiology and pathogenesis of fungal pathogens. However, the underlying mechanisms by which iron homeostasis modulates fungal pathogenesis remain to be fully elucidated. We therefore focused on investigating the functions of mitochondrial iron transporter ClMrs3/4 in virulence. We conducted targeted gene deletions, expression analyses, biochemistry, and pathogenicity assays, demonstrating that ClMrs3/4 regulates appressorial development via maintenance of cellular iron balance in Curvularia lunata. ClMrs3/4 modulates virulence by influencing appressorial development in C. lunata, which is dependent on iron homeostasis. ClMrs3/4 controls nitric oxide (NO) balance via the nitrate (NO3−) assimilation pathway by modulating cytoplasmic iron levels, a process crucial for turgor pressure accumulation within the appressoria independent of mitochondrial and cytoplasmic Fe–S cluster biosynthesis. Our findings underscore the conserved role of Mrs3/4 in iron homeostasis among pathogenic fungi and propose a novel mechanism by which iron homeostasis regulates virulence, particularly through the NO3− assimilation pathway mediated by cytoplasmic iron levels to regulate appressorial development.
Keywords: appressorial development; Fe–S cluster; iron homeostasis; mitochondrial iron transporter ClMrs3/4; nitrate metabolism; nitric oxide; virulence